STRATEGI PENGEMBANGAN USAHA OBAT HERBAL MINHAJUL KAROMAH, PAGURON JALAK BANTEN NUSANTARA DALAM EKONOMI SYARIAH - Rekawati1, Ratu Ageng; Waki, Ahmad; Misno (Institut Agama Islam Sahid Bogor, 2024)
The trend of using herbal medicines is currently increasing, it is predicted that the peak of progress from the use of herbal medicines will occur in 2050. In order to get there, the production of herbal medicines is a must, this is because it is proven that medicines made from herbs are more beneficial. Minhajul Karomah Herbal Medicine Business is one of the herbal medicine manufacturers in Banten. What is the business development strategy? The research method used is qualitative with qualitative analysis and SWOT (Strength, Weakness, Opportunity Threat). Data were obtained through direct observation, in-depth interviews and document studies. The results of this study are that the strategy used in the Minhajul Karamah herbal medicine business is; adding product variants, improving the quality of human resources, providing the best service and innovating sales. This strategy from an Islamic perspective is that it must be aligned with sharia values, especially those related to halal products and sharia management patterns that are applied in their management. The SWOT analysis shows that the strength of Minhajul Karomah Herbal Medicine is the captive market, namely the large number of PJBN members and the opportunity for herbal medicines. The weakness is that the business has not been running for a long time, the management is not neat and the production system is not stable. The opportunities that exist are the increasing public interest in herbal medicines and the opening of international markets. The threats from this business are competitors from large companies and policies that still do not support herbal medicines.